傾斜機能構造を有する生体模倣セラミックスの特性と巨細胞出現の評価 - 永易, 裕樹; 赤澤, 敏之; 草野, 薫; 南田, 康人; 村田, 勝 (Journal of Japanese Society of Oral Implantology, 2014)
We developed a hypothesis that dissoluble absorption and giant cellular absorption are indispensable for bio- ceramics harmonized with bone remodeling. The aim of this study was to investigate the characteristics of porous and modified ceramics and the number of giant cells in subcutaneous tissue. Commercial products of b-tricalcium phosphate (β-TCP (porosity:75%)) were easily modified to functionally graded calcium phosphate ceramics by the partial dissolution–precipitation (PDP) technique, which involved a stirring of 300 rpm in 2% HNO3 solutions (50 cm3) containing Ca2＋ and PO43- ions and a supersonic treatment at 120 W and 38 kHz in the same solutions. The dissolution efficiency of porous bTCP block by the supersonic treatment drastically increased with time, depending on the porosity of ceramics. For even dense β-TCP block, enhancement of micro-pores and propagation of nano-cracks were recognized by the supersonic treatment for 7 min. After the specific PDP technique, Nano-crystals of HAp were successfully precipitated on all over the pore wall surface in the macro- and micro-pores of the ceramics. The PDP-TCP (Partial Dissolution-Precipitation technique-TCP) ceramics were implanted into the back subcutis in 4 week-old Wistar rats. At 3 weeks after the implantation, the PDP-TCP exhibited a significant increase in the number of osteoclast-like giant cells and better affinity for body fluid than original β-TCP products. The results suggested that our PDP treated β-TCP could have a potential for a bioactive scaffold with good giant cell-absorption.